Cooperative Learning Model on Group Work Ability of Vocational High School Students: Learning Basic Electronics - Rande, Marlina; Mustamin, Mustamin; Lu’mu, Lu’mu (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The ability to work together in groups is a crucial soft skill for vocational high school students, but conventional learning methods are often less effective in honing this collaborative competence in complex technical subjects. This study aims to test the effectiveness of the Cooperative Learning (CL) learning model on improving students' group work skills in Basic Electronics. This study used a quasi-experimental method with a nonequivalent control group pretest-posttest design. The sample consisted of 50 students of grade XI TAV Vocational High School 4 Gowa who were divided into an experimental group (CL implementation) and a control group (conventional learning). The research instruments included a validated learning outcome test and a group work ability questionnaire. Data were analyzed using Normalized Gain Score (N-Gain) and Analysis of Covariance (ANCOVA). The findings showed that the N-Gain value of the experimental group reached 61.77%, higher than the control group, which was only 44.06%. The effectiveness difference of 17.71% indicates an increase in group skills in the moderate category but significantly outperformed the control class. The ANCOVA test results confirmed this finding with a significant value of 0.001 (p < 0.05), proving a significant influence of the CL model on students' collaboration skills. This study confirms that cooperative learning is an effective strategy for strengthening collaboration soft skills in vocational education environments while also providing practical recommendations for educators on integrating teamwork into technical curricula.